The Emerging Islam in America - Sholawati Sholawati (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2020)
Islam has an essential role in the development of human civilization. As a relatively new religion, Islam has developed very rapidly for over 1500 years. Currently, Islam is recorded as the second-largest religion in the world after Christianity, with followers of more than 1.5 billion. Based on several official survey institutions, in 2025, it is predicted that Muslims will reach 30% of the earth’s population and become the largest religion in the world. Islam was born in the Arabian Peninsula and has spread throughout the world. Muslims can be found in almost all countries, including underdeveloped countries, developing countries, and developed countries. Even the United States, with the most substantial economic, political, and military power globally, is inseparable from Muslims in its development process. Edward E. Curtis, in his book Muslim Americans in The Military, mentioned various historical evidence showing Muslim participation in America. According to this Professor of Religion from the University of Indianapolis, Muslims had played a significant role, from discovering the Americas to defending the north’s victories in the United States Civil War.2 Also, he added that even though Christopher Columbus was the sailor who discovered America, that discovery would be impossible to happen without Muslims.